Reliability based inspection optimisation of floaters - Ονουφρίου, Τούλα (My University, 1999)
This paper presents the development and application of reliability based inspection planning techniques for floaters. Based on previous experience from jacket structure applications, reliability based inspection techniques for floaters are developed. The differences between floaters and jacket structures in relation to fatigue damage, redundancy levels and inspection practice are examined and reflected in the proposed methodology. The application and benefits of these techniques are demonstrated through representative analyses and important trends are highlighted through the results of a parametric sensitivity study.
Keywords: Reliability; Ships; Materials--Fatigue